PERBANDINGAN BUDIDAYA TANAMAN CABAI RAWIT (Capsicum Annuum L) YANG MENGGUNAKAN TEKNOLOGI MODERN DAN TRADISIONAL DI KAMPUNG MANDOPI DISTRIK MANOKWARI UTARA KABUPATEN MANOKWARI - Dugupa, Pelanus; Matualage, Amestina; Holle, Yolanda (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2024)
Comparing the cultivation of cayenne pepper (Capsicum Annuum L) is the goal of this study. With a total land area of 10 m x 6 m, cayenne pepper is the primary crop grown in one large area. Two (two) comparisons of cayenne pepper cultivation processes are made, one using modern technology and the other using traditional methods. This study, which took the form of an experiment, was conducted at the Mandopi Village Location in the North Manokwari District of the Manokwari Regency in West Papua Province over the course of three months, from November 2023 to January 2024. This study uses both primary and secondary data. Observation and measurement of production results are the main methods used to collect data. Secondary data is gathered from institutions or agencies that are related. Simple tabulation is the data analysis method employed, which compares the production of cayenne pepper grown with modern technology and with traditional methods. Cayenne pepper plants are grown on 10 m x 6 m plots of land using both conventional and modern methods. While 0.3 grams of chili are produced using traditional technology, 1.4 kg of cayenne pepper is produced using modern technology.